AUTHENTICITY IN IMPROVING STUDENTS SPEAKING ABILITY IN EFL TEACHING - Sugdiyona Turgunboeva (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This research article explores the significance of authenticity in enhancing the speaking ability of English as a Foreign Language (EFL) students. The study investigates various strategies and approaches employed to incorporate authenticity in EFL classrooms and examines the positive outcomes resulting from the implementation of these strategies. Authenticity is considered crucial for creating a realistic and meaningful language learning environment that promotes effective communication skills, cultural understanding, and student motivation